Passivity and Synchronization of Multiple Multi-Delayed Neural Networks via Impulsive Control - Yong Wang; Zhichun Yang; Tonglai Liu; Hong-An Tang (Discrete Dynamics in Nature and Society)
This paper is concerned with the passivity and synchronization for multiple multi-delayed neural networks (MMDNNs) under impulsive control. To ensure the passivity, input strict passivity, and output strict passivity in MMDNNs, a suitable impulsive controller is designed. Moreover, an impulsive time-dependent Lyapunov functional is exploited to obtain the synchronization criterion of MMDNNs, where the criterion is formulated by linear matrix inequalities. Numerical examples are given to verify the validity of the theoretical results.